Imaginaries of the resilient second nuclear era: Nuclear paradox resolution and a feasible atomic priesthood - Juan Chen; Isaac Yap (Nuclear Engineering and Technology, 2025)
The enduring philosophical and political struggle between embracing nuclear energy as a climate solution and an economic catalyst, and resisting it over risks of weapons proliferation and catastrophic accidents, has been a prominent fixture since the aftermath of Hiroshima and Nagasaki. Termed as the nuclear paradox, this dual framing of nuclear energy often oscillates between promise and peril depending on which aspect of its duality appears more immediate, leaving society to navigate the difficult trade-offs. This study re-examines the structural shortcomings of the first nuclear era and outlines the conditions necessary for a more resilient second phase of nuclear development in the context of today's evolving energy market. It argues that the Liquid Fluoride Thorium Reactor (LFTR), through its distinctive reactor design and fuel cycle, offers a comprehensive response to long-standing concerns about safety, economic viability, proliferation, and waste permanence—exemplified by the ill-fated concept of the Atomic Priesthood. The analysis concludes with concrete policy recommendations to accelerate LFTR research and implementation, contributing to the realization of a more secure and sustainable nuclear energy future.